Program penguatan disiplin positif siswa melalui kegiatan pembiasaan sholat dhuha berjamaah di sekolah dasar - Nursafitri, Risa; Raviani, Ngainur; Khoirudin, Muhammad Asa; Lina, Marisa Fran (Journal of Smart Education and Learning, 2025)
This community service program aims to promote positive discipline among elementary school students by fostering the habit of performing Dhuha prayers in congregation. The method used is a participatory approach, with teachers actively assisting students, and photo documentation is used as observation material during the activities carried out directly in the school environment. This activity is participated in by all students from grades 1 to 6. The results of the activity show an improvement in student discipline, especially in punctuality, personal and environmental cleanliness, and polite and orderly behaviour during Dhuha prayers. In addition, students become more aware of their spiritual and religious responsibilities at school. Through the routine practice of worship, this activity can also strengthen the relationship between teachers and students and create a religious and conducive learning atmosphere. This program is expected to be implemented continuously with the support of the school and teachers to cultivate a positive discipline culture and religious character in students from an early age. In addition, the habitual practice of performing congregational Dhuha prayers also serves as a means for comprehensive character development of students, instilling values of responsibility, obedience to rules, cooperation, and exemplary behaviour through religious activities carried out together in the school environment.